Draft Annual Plan (2004-05) Volume-I Government of Uttaranchal - Planning Commission (Planning Commission, 2004)
Uttaranchal came into existence on November 9th, 2000 as the 27th State of the Indian Union. It was carved out of the State of Uttar Pradesh and comprised of the two hill Divisions and District of Haridwar. The State is strategically located and forms part of the Northern boundary of the country sharing its borders with Nepal and Tibet(China). It extends between 77°34’and 81°02’E Longitude and 28°43’to 31°27’N Latitude. It touches Tibet in the north, Himachal Pradesh in the west and northwest, Gangetic plains of Uttar Pradesh in the south and Nepal in the east. Starting from the foothills in the south it extends to the snow clad mountains in the north.
Planning Department Government of Uttaranchal